Capillariasis sapi di Surabaya - Rochiman Sasmita (Hemera Zoa, 1978)
A survey on the worm infestation of the digestive tracts of beef cattle and dairy cattle was carried out in Surabaya which started on October 1975. The author found Cappilaria bovis (Schnyder, 1906) eggs in nine out of 246 beef cattle fecal samples, but none from 257 dairy cattle fecal samples. The measurements of the eggs were 42.84-54.05 microns long with a mean of 51.92 microns and 21.15-25.05 microns wide with a mean of 23.34 microns. The eggs had bipolar plugs, thick walls and contained a single cell and were brown coloured. This is the first report on Capillaria bovis eggs in Indonesia.